PENERAPAN MODEL PEMBELAJARAN KOOPERATIF SNOWBALL THROWING DENGAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI - Nuha Puspaningtyas; Krisdianto Hadi Prasetyo; Isna Farahsanti (Absis: Mathematics Education Journal, 2020)
The objectives of this study are to increase the activeness and students learning achievement through the Snowball Throwing type cooperative learning model with Discovery Learning. This research is a Classroom Action Research (CAR) which consists of 4 stages with 3 cycles. The subjects are 29 students of class VII B SMP Negeri 16 Surakarta for academic year 2019/2020.  The data collection techniques in this study are test, observation, and documentation techniques. The data analysis technique is carried out by analyzing the observation sheet and the analysis of the success of the action. Based on the research, the percentage of pre-cycle activeness data is 33.38%, the first cycle is 42.90%, the second cycle is 52.40% and the third cycle is 71.50%, while for classical completeness pre-cycle learning achievement is obtained 20.69% , cycle I 27.58%, in cycle II it increased to 44.83% and cycle III increased to 75.86%. From the results obtained, it can be concluded that the application of the Snowball Throwing type cooperative learning model with Discovery Learning can increase the activeness and students learning achievement of class VII B students of SMP Negeri 16 Surakarta in the academic year 2019/2020.